Cooling System for Data Centers Based on the Air-Water-Air Principle with Increased Temperature Differential - Jing Yang; Xie Xiaoyun; Jiang Yi (Zhileng xuebao, 2025)
Improving the energy efficiency of data centers by conserving energy in cooling systems is a priority strategy. In this study, thermal analysis of the prevailing air-water-air cooling system revealed inefficiencies caused by a significant discrepancy in the flow rate between the air and water sides of the server room air conditioning system. To mitigate such discrepancy, a new system architecture with a high-temperature differential on the waterside was proposed. Compared with a conventional system with a small temperature differential, the proposed high-temperature differential cooling system substantially augmented the proportion of natural cooling throughout the year, reduced the energy consumption of pumping fluids, and reduced the total energy consumption of the cooling system by approximately 20%-30%. Although the introduction of a high-temperature differential cooling system requires an increase in the heat exchange area and an increase in the cost of air conditioning for the server room, it concurrently reduces the investment in cooling towers, chillers, circulating pumps, chilled water storage tanks, pipelines, and valves, ultimately reducing the total investment in the cooling system by 15%-25%. Furthermore, the high-temperature differential cooling system facilitates operational adjustments, decouples control from external temperature variations and IT load changes, and minimizes maintenance requirements.